Corporate social responsibility in the Egyptian banking sector: A study on effectiveness and profitability - Youssef, Yasmin (AUC Knowledge Fountain, 2018)
Corporate Social Responsibility is a booming concept worldwide and all corporates are shifting towards undertaking some Corporate Social Responsibility activities. Banks play a major role in the Corporate Social Responsibility sector, as they are the base of any loan for any corporate, hence, they have the control of the Corporate Social Responsibility activities of a firm. Banks do Corporate Social Responsibility activities within different disciplines. This study analyzes the effectiveness of Corporate Social Responsibility activities, along with the relation between the bank’s Corporate Social Responsibility activities and its profitability. Intensive interviews were conducted with Corporate Social Responsibility representatives/managers at the banks to get more in-depth information on the research variables -effectiveness and profitability- to enhance our understanding of the Corporate Social Responsibility sector in Egypt. The results indicate that there is a shift in the concept of CSR from philanthropy or just charity giving to sustainability, taking into consideration the economic, social, governance and environmental aspects of the society.